Digestive endoscopic removal of cocaine pellets: Safety evaluation - Aboikoni, Alolia; Wallyn, Marion; Bonifay, Timothée; Chhorn, Piseth; Sylla, Balandougou; Alogo A Nwatsok, Marthe; Becar, Alix; Ngock Dime, Paul; Nguyen, Thi Thu Nga; Fremery, Alexis; Garzelli, Lorenzo; Aissaoui, Houari; Zappa, Magaly; Louvel, Dominique (Endoscopy International Open, 2025)
Removal of cocaine pellets by endoscopy is the subject of much debate, due to the supposed risk of rupture. This study aimed to evaluate the safety of digestive endoscopic removal of cocaine pellets.This was a single-center, observational, retrospective study conducted at the Cayenne Hospital in French Guiana from July 2015 to May 2023. We included patients in whom digestive endoscopy was performed for delayed evacuation despite conservative treatment defined by persistence of pellets on imaging from the third day of hospitalization. Endoscopy was performed only if the pellets present were at low risk of rupture (type 4 according to the classification by Pidoto in 2002). We collected demographic, imaging, endoscopic and follow-up data.We included 111 patients, 75% of whom were male. Median age was 25 years (range, 20–33). Imaging was performed in 99% of cases. On imaging prior to endoscopy, pellets were found mainly in the stomach (28%), right colon (28%), left colon (30%), and sigmoid (31%). Median time to endoscopy was 3 days (range, 2.5–4). Median number of pellets extracted endoscopically was one (range, 1–4). The material used was mainly endoscopic baskets (60%). No patient presented any per or post-endoscopic complications. No pellets ruptured during extraction. There was no sign of cocaine intoxication during or after endoscopy. The success rate for pellet removal was 92% during the first endoscopy and 100% during the second endoscopy.Endoscopic removal of micro-industrially-produced cocaine pellets seems to be a safe and effective method. Therefore, endoscopy has a place in management of these patients.
Keywords: Endoscopy Upper GI Tract; Foreign-bodies; Endoscopy Lower GI Tract